Synthesis and application of boron-nitrogen doped carbon nano-onions in supercapacitors - Shaku, Bokome (My University, 2020)
This work reports on the synthesis of carbon nano-onions (CNOs) via the chemical vapor deposition (CVD) and flame pyrolysis methods for application in supercapacitors (SCs).The synthesis of CNOs using CVD was achieved by reducing a Fe-Co catalyst to its metallic state, followed by decomposition of acetylene (C2H2) as a carbon source. The metal catalyst was supported on calcium carbonate (CaCO3). The synthesis of CNOs was carried out at different reaction temperatures (i.e. 450 °C, 550 °C and 650 °C). In addition to the final product encapsulating metal catalyst particles, the synthesized CNOs contained a number of by-products such as carbon nano-fibres and carbon nano-tubes. To overcome the problem associated with the undesired formation of carbon materials, a flame pyrolysis approach was used for the synthesis of CNOs with high purity, using grapeseed oil as a carbon source. The pristine material was annealed at different temperatures and doped with boron (B) and nitrogen (N). Physical properties of the materials were investigated and characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), a gas adsorption technique, Brunauer-Emmet-Teller (BET) analysis, Raman spectroscopy and thermogravimetric analysis (TGA). The results from the CVD method demonstrated a change as the temperature and flow rate increased. Microscopy analysis revealed successful dispersion of Fe and Co particles onto CaCO3 which produced a mixture of materials (CNOs, CNFs and CNTs). The XRD patterns confirmed the presence of highly active crystalline mixed oxide (CoFe2O4) as the dominant catalyst phase. TEM analysis of CNOs from the flame pyrolysis method revealed multi-layered concentric carbon layers with no by-products. The amount of substitutional nitrogen in the CNO samples was 1.67% which resulted in an increase in the specific surface area and ID/IGratio. The work further explored the use of CNOs, from flame pyrolysis, as electrode materials in a two electrode system. The capacitance and resistivity of the prepared carbon electrodes were evaluated using techniques such as cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) and electrochemical impedance spectroscopy (EIS). The electrochemical performance of N-doped CNOs was investigated and compared with those of the pristine, annealed and B-doped CNOs within an operating cell potential of 0.8 V in a 2 M KOH electrolyte. The specific capacitance increased upon nitrogen doping to 54 F/g as compared to pristine CNOs (7.5 F/g), annealed CNOs at 750 °C-2 h (22.5 F/g) and B-doped CNOs (28 F/g). The N-doped CNOs exhibited superior electrochemical performance compared to pristine, annealed and B-doped CNOs which was related to the high surface area and ID/IG ratio and indicated that the electrolyte ions could readily penetrate the pores of the electrode material. Our results demonstrated that N-doped CNOs are capable of delivering energy in a short timeframe in supercapacitors
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment for the degree of Master of Science in Chemistry, 2020
Keywords: Boron compounds; Carbon compounds